Efektifitas Spray Ekstrak Daun Lamtoro (Leucaena Leucocephala) terhadap Jumlah dan Waktu Kematian Caplak Rhipicephalus sanguineus pada Anjing - Olan Rahayu PAN (VITEK : Bidang Kedokteran Hewan, 2016)
This study aims to test the effectiveness of using Spray Extract Leucaena Leaf (Leucaena leucocephala) on dogs with Tick Rhipicephalus sanguineus. The method used is an experimental design with Group Random Design (GRD), with the number of sample 8 dogs of different ages and sex. Samples were divided into four treatments and two replications. Data analysis techniques used in this study is the Analysis of Variance (ANOVA), with an examination of macroscopic was conducted by observing the amount and time of death Ticks Rhipicephalus Sanguineus in dogs were carried out on the day of observation 7th, 14th and 21st. The results of the study with α = 5% concluded that: (1) Based on the results of one way ANOVA test in the experimental group, showed that the influence of leaf extract dose leuceana to the number of ticks deaths; Based on the observation time, there is the influence of observation time to the number of ticks. (2) F count > F table = 129.7 (P <0.05) showed that the treatment group of dogs were given the extract leuceana leaf spray dose 60% (P3) and most effective when compared with those dogs from the negative control group without treatment (P0), a group treated extract leuceana leaf spray dose of 20% (P1), and a group treated extract leuceana leaf spray dose of 40% (P2).